Application of the thermography method for determining the fatigue limit of a nickel alloy produced by wire‑arc additive manufacturing (Fracture and Structural Integrity, 2025)
The development of additive technologies for manufacturing safety‑critical components operating under vibration must be accompanied by a careful analysis of the material’s resistance to high‑cycle fatigue (HCF). This paper presents a technique for the rapid assessment of the fatigue limit of nickel alloys fabricated by wire‑and‑arc additive manufacturing (WAAM). The technique grounded in infrared thermography (IRT), utilizes the self‑heating effect during cyclic loading. The technique realisation involves choosing specimen design, test equipment, the number and parameters of loading blocks, self‑heating indicators, and result‑processing procedures that account for material specifics. It is shown that the rate of temperature rise at the specimen surface at the start of each loading block can serve as an indicator of self‑heating. Experimental data on the fatigue limit of specimens made from the heat‑resistant alloy Inconel 625 produced by WAAM are obtained. Validation of the developed method is performed by comparing the fatigue limit derived from IRT with the results of conventional fatigue testing and the corresponding S–N curve. For additive nickel alloys, the proposed accelerated fatigue‑limit assessment allows a substantial reduction in the number of specimens and the time required to select technological parameters and refine additive manufacturing processes compared with traditional fatigue testing.
Keywords: Additive Manufacturing; Wire-are deposition; Heat-resistant nickel alloy; High-cycle fatigue; Fatigue limit; Infrared thermography method